Analysis of epidemiological characteristics of poisonous mushroom poisoning in Hubei Province from 2016 to 2020 - OUYANG Yingying; GONG Chenrui; DAI Shiyu; LI Jingjing; ZHANG Chi; LIU Shuang (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo provide scientific basis for early warning and prevention， the epidemic characteristics of mushroom poisoning in Hubei Province from 2016 to 2020 were analyzed.MethodsThe epidemiological characteristics of mushroom poisoning incidents reported by the food-borne disease outbreak surveillance system in Hubei Province from 2016 to 2020 were analyzed.ResultsA total of 163 cases of poisonous mushroom poisoning were reported in Hubei Province from 2016 to 2020， with 487 cases and 17 deaths， with a case fatality rate of 3.49%（17/487）. The largest number of incidents occurred in 2020， accounting for 34.36% （56/163） of the total. Poisonous mushroom poisoning mainly occurred from June to October. Enshi Prefecture and Yichang City were the areas with high incidence of poisonous mushroom poisoning， and households were the main sources of poisonous mushroom poisoning places that occurred accounted for 93.87%（153/163） of the total number of incidents. The proportion of rural poisonous mushroom poisoning incidents was much higher than that in urban areas， and accidental picking and eating was the only cause of poisoning mushroom poisoning.ConclusionPoisonous mushroom poisoning is the main cause of death from food-borne disease outbreaks in Hubei Province. Publicity and education should be carried out in key areas for the high-level populations during the high-incidence season. Wild mushrooms should not be picked or eaten.